The Role and Impacts of Growth Hormones in Maximizing Animal Production- A review - Duguma Dibbisa Itana; Ararsa Duguma (Turkish Journal of Agriculture: Food Science and Technology)
The purpose of the study is to examine the role and impacts of growth hormone in maximizing animal products. Growth hormones are biological stimulants that are found either naturally in the organism or synthetically manufactured. Phytoestrogens, phytoprogestrons and Phenolic compounds are hormones from plants. Drugs from of placenta and colostrums of cow`s contain progesterone, estrogene, gonadotropin, and prostaglandins hormones. Growth hormones have got popular applications in dairy, beef, feed improvement and Biopharmaceutical productions with the aim of producing valuable products: fat free meat (Porcine Somatotropin hormone in pigs), nutritionally and medicinally reach milk (Bovine Somatotropin hormone in cattle), palatable and disease and insect pest resistant forage crop production. They have got also contribution in maximizing livestock production by involving in adjusting animals’ reproductive process such as oestrus synchronization and superovulation mainly during artificial insemination and embryo transfer. Controversially, these hormones have wide impacts on human being, animal welfare, environment and etc. Contamination of ground water by hormones that are found in the animals` excreta will cause deleterious effects such as cancer, loss of fertility, and some imbalance of minerals in the water and soil.